Governmental subvention and assistance (GSA): disclosure and profitability in major brazilian companies - Loureiro, Débora Queiroz; Gallon, Alessandra Vasconcelos; De Luca, Márcia Martins Mendes (Revista de Contabilidade e Organizações, 2011)
This study investigates the disclosure and economic effects stemming from recognition of governmental subventions and assistances (SAG) in accounting demonstrations by major Brazilian companies, according to Statement CPC 07, altered by CPC 07(RI), in 2010. We analyzed 88 of the 100 major companies listed on "Exame Melhores e Maiores 2010". Financial and insurance companies were not included. The levels of disclosure were obtained in a content analysis of explanatory notes of2008 and 2009 by means of a check list, according to release dispositions in CPC 07, and economic effects measured by the ROA, ROE, ROS and ISAG indices of 2009. It was observed that companies present a disclosure level which is considered low. The level was limited to an average 30.4% in 2008 and 33.3% in 2009 of the CPC 07 release requisites. Concerning economic effects, was found a positive variation in profits, especially in ROE, and was observed an expressive participation of SAGs in the equity of companies of Textile and Pulp and Paper sectors.